DIFFERENCES IN DIRECT CARE PROFESSIONAL BURNOUT AND PERSONALIZED CARE IN LONG-TERM CARE SETTINGS. (11th November 2018) - Stratton, L; Dannewitz, H; Margrett, J; Brown, L; Shelley, M
Abstract: Direct care professionals in long-term care (LTC) facilities frequently experience burnout, often due to job demands (Woodhead, Northrop, & Edelstein, 2014). However, providing person-centered care has been shown to positively affect direct care professional outcomes (Fazio, Pace, Flinner, & Kallmyer, 2018), which may be beneficial in combating burnout. The Targeted Training Intervention 360 (TTI) program was implemented in 10 LTC facilities in Iowa and aims at increasing dementia capability and person-centered care. Baseline data were collected from direct care professionals (N = 56) regarding feelings of burnout, using the Maslach Burnout Inventory (MBI) which is comprised of three subscales, and personalized care, using the Person-Centered Care Assessment Tool (P-CAT) which also contains three subscales. In this study, we investigated the association between high and low scores on each MBI subscale and each P-CAT subscale. Analyses revealed that direct care professionals with lower scores on the MBI subscale measuring less emotional exhaustion reported significantly higher scores on the P-CAT subscale measuring higher organizational person-centered support (M = 13.63) compared to those with higher emotional exhaustion scores on the MBI (M = 11.67; p = .025). Additional analyses indicated significant differences in MBI and P-CAT subscale scores when direct care professionals were grouped according to facility Centers for Medicare and Medicaid Services rating as well as number of years employed. Discussion focuses on continued efforts to increase personalized care in LTC facilities and how direct care professional burnout and organizational factors may play a role in this effort.